THE EFFECT OF IMPLEMENTATION QUALITY ASSURANCE AND BUSINESS INCUBATORS ON ENTREPRENEUR QUALITY AND ITS IMPACT ON SMES PERFORMANCE IN EAST JAVA (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study examined the implementation of quality assurance and business incubators to quality entrepreneurs and their impact on the performance of SMEs in East Java. The results of this study indicate that the implementation of quality assurance in the implementation of training on the enterprenuer affect the quality of the implementation of a business incubator entrepreneur nd also affect the quality of the entrepreneur in managing its business, so by increasing the quality of the entrepreneur affect the performance of SMEs are getting better in East Java. Respondents in this study involving 100 entrepreneurs of SMEs in East Java. With the proviso noun turnover of USD 50 million and a workforce of at least two people. Of University Merdeka Malang as Education Cleaner has a quality assurance program and the business incubator strives to be a university that can contribute and benefit in helping and developing the performance of SMEs in East Java. With the implementation of quality assurance of the Entrepreneur by insight and direct implementation in the form of learning and training in business, so that the entrepreneur really more qualified. While the business incubator program menitiberatkan the direct implementation on the business or businesses that directly occupied by the entrepreneur who monitored the process in a business incubator. So that through the implementation of quality assurance and business incubator will be achieved Entrepreneur good quality and will ultimately improve the performance of SMEs.